Pendidikan Dan Etika Berpolitik - Agustinus Pratisto Trinarso (Arete, 2013)
Political education and political ethics interrelated . In Political ethics, human behaviors to gain power are understood and judged. In political education, our judges to all human behaviorsto gain power are presented, learnt and inherited to the next generation. In contemporary Indonesian context, these two fold fieldsare urgent to discuss. The discussion must consider some important matters, such as pluralism in Indonesian society, human right fulfillment, model of democracy wanted to build and the efforts to gain social justice.